Elaboração e implementação de protocolo de controle glicêmico em pacientes não críticos hospitalizados em hospital terciário - Carpentieri, Giovanna Braganholo [UNIFESP] (2016)
Introduction: Hyperglycemia in diabetic and non-diabetic patients hospitalized in noncritically ill condition is common in general hospitals. Several observational studies with inpatients show a strong correlation between hyperglycemia and increased risk of adverse clinical outcomes, such as prolonged hospitalization, higher infections rates, increased morbidity and mortality and increased hospital costs. Although current guidelines recommend that hyperglycemic patients should be treated with basal-bolus insulin regimen, a more physiological and effective method, in most hospitals it still prevails the use of the sliding scale, treatment associated with increased glycemic variability and poor prognosis. Purpose: Develop and implement an institutional protocol for glycemic control in noncritically ill inpatients. Methods: The study was conducted at Hospital São Paulo of the Paulista School of Medicine - Federal University of São Paulo. The project was developed in three phases. The first phase consisted of the theoretical foundation and development of a pilot protocol according to the current guidelines and based on existing protocols at other institutions. In the second phase, meetings were held with the Clinical and Technical Directors and with the management teams of nutrition, laboratory and nursing to adapt the pilot protocol to the needs and technical and human conditions of the hospital. The last phase was based on an outreach program for the professionals involved in the inpatients care. Results: a protocol for glycemic control for noncritically ill patients customized according to the complexity and the material and human resources of the Hospital São Paulo was prepared. The protocol was designed in the form of flow charts, one for the treatment of hyperglycemia, using the basal-bolus insulin therapy regimen, and a second one for the treatment of hypoglycemia. It was approved by the board of the Hospital São Paulo. The outreach plan included training of professionals involved in the care of hospitalized patients through printed materials, lectures and teaching materials available on the Internet. After training, the project was implemented in 30 medical and surgical wards of the institution. Conclusion: The development and implementation of an institutional protocol for glycemic control is a potentially effective way to increase security by treating hyperglycemic patients and improve the quality of care provided by health professionals. This deployment model can guide other hospitals in their initiatives for the management of blood glucose levels in hospitalized patients.